Indeks Entomologi Vektor Nyamuk Aedes spp di Daerah Endemis Demam Berdarah Dengue (DBD) di Kecamatan Tanjungpinang Timur Kota Tanjungpinang Provinsi Kepulauan Riau - Risman Kurnia; Tri Baskoro Tunggul Satoto; M Lutfan Lazuardi (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
Dengue hemorrhagic fever (DHF) is still a health problem in Indonesia. This study aims to determine the vector entomology index of Aedes spp mosquitoes in dengue endemic areas in the East Tanjungpinang District, Tanjungpinang City. The study was conducted in January-March 2020 with a cross sectional method. The research locations in DHF endemic areas are Batu 9 and Bulang villages. Entomological data were analyzed descriptively. The results showed that the value of the House index for Batu 9 was 45% and Kampung Bulang was 38.8%. The Containteir index value is 12.6% in Batu 9 and Kampung Bulang. The Breteau index value in Kelurahan Batu 9 was 76% and Kampung Bulang was 68%, while the Larva free rate in Batu 9 was 55% and 61% in Kampung Bulang Village. Density of dengue vector larvae based on HI, CI and BI in both DHF endemic villages is on a scale of 4-7 and is included in the medium and high risk categories. This explains that the entomological index in East Tanjungpinang District is still low, so it is necessary to control Aedes spp larvae by draining the bath, closing water storage, conducting mosquito nest eradication, and burying used goods so that they do not become a breeding place for DHF vectors.